Manajemen Pengembangan Kompetensi Guru Di Madrasah Aliyah Negeri I Langkat - Raudina Maihani, Ahmad Fuadi, Zaifatur Ridha (Ability: Journal of Education and Social Analysis, 2023)
The management of teacher competency development at Madrasah Aliyah Negeri I Langkat has been carried out very well by the madrasa so that teachers are able to have the competencies expected in educating. The management of teacher competency development is carried out through several competency development programs for teachers including subject teacher deliberations (MGMP) involving teachers in both public and private fields of study. Asking each teacher to prepare a learning implementation plan (RPP), prepare visual aids before teaching and giving apperceptions. In addition, efforts to develop teacher competence by managing time allocation for each subject taught by allocating more time for prioritized subjects both during the teaching and learning process in class and in the laboratory. Another form of management for developing teacher competencies is by appealing to each teacher to have their own creative and innovative learning methods so that they can be properly applied during learning. Increasing teacher competence can be seen from several indicators of improvement. The first indicator is seen from the teacher's mastery of the material covered and mastery of the class. Competent teachers will produce quality students as seen from the increase in student achievement. Increasing student achievement from various sides shows that the teachers who educate them have good competence. Other indicators can be seen from the development of students' interest and motivation in learning. indicators that teachers have good competence, can be seen from the development of students' talents. Teachers who have competence, especially social competence, will be able to become role models for their students. This competence can be seen from changes in attitudes, characteristics and morals of students who continue to experience changes for the better.